2022
DOI: 10.21608/ejhm.2022.211054
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Left Ventricular Function by Global Longitudinal Strain in Patients with non-ST Elevation Myocardial Infarction:

Abstract: Background: Left ventricular ejection fraction (LVEF) is a strong prognostic parameter in patients with heart disease. The assessment of global longitudinal strain (GLS) from speckle-tracking analysis of 2-dimensional echocardiography has become a clinically feasible alternative to LVEF for the measurement of myocardial function. Objective: The aim of the current work was to compare between GLS speckle tracking echocardiography and Simpson's biplane methods for assessment of left ventricular function in non-ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The results of our study agree to some extent with many studies conducted to assess ejection fraction in patients, including patients with myocardial infarction [11][12][13] . Another study conducted by ( 14) to evaluate EF in patients with heart failure revealed that the elderly patients have preserved EF HFpEF, while the el-derly patients in our study have a midrange EF type HFmrEF.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of our study agree to some extent with many studies conducted to assess ejection fraction in patients, including patients with myocardial infarction [11][12][13] . Another study conducted by ( 14) to evaluate EF in patients with heart failure revealed that the elderly patients have preserved EF HFpEF, while the el-derly patients in our study have a midrange EF type HFmrEF.…”
Section: Discussionsupporting
confidence: 91%
“…If the ejection fraction of the left ventricle of the heart is 40% and <50%, it is considered heart failure with mid-range ejection fraction (HFmrEF), but if the is LVEF ≤ 50%, it is considered a preserved ejection fraction HFpEF 11 . so far, at present it remains ejection fraction EF is the first measure for diagnosing heart failure HF, one of the most common causes of which is a weakness or defect in the left ventricular muscle of the heart, which often occurs in patients with acute myocardial infarction 12,15 . HF and liver disease are among the most common mortality causes worldwide 16 .…”
Section: Discussionmentioning
confidence: 99%
“…One of the primary causes of mortality worldwide is AMI though the use of early PPCI is growing and has greatly reduced mortality [19]. The evaluation of GLS, which depicts the function of longitudinally oriented cardiac fibers within the subendocardium and is particularly susceptible to ischemia, has received the majority of attention [4,5)]. According to recent studies, GLS has been linked to regional cardiac function recovery and in-hospital outcomes in patients with AMI [20.21].…”
Section: Discussionmentioning
confidence: 99%
“…However, the LVEF is both preload and afterload dependent, with substantial interobserver variability. Two-dimensional speckle tracking echocardiography (2D-STE) is a B-mode based approach that can assess regional myocardial deformation through measuring of global longitudinal strain (GLS), which has been shown to be less affected by loading conditions [3][4][5][6][7]. recent studies reported that myocardial deformation imaging by 2D-STE after acute myocardial infarction (AMI) predicts cardiovascular outcomes such as new onset heart failure (HF) and cardiovascular death [8,9].…”
Section: Introductionmentioning
confidence: 99%